Pain Reduction Using Low Level Laser Irradiation in Single-Visit Endodontic Treatment - Asnaashari, Mohammad; Mohebi, Shadi; Paymanpour, Payam (Journal of Lasers in Medical Sciences, 2011)
INTRODUCTION: Post-endodontic treatment pain is a relatively common condition which needs analgesics for patient’s pain relief. Low-level laser therapy (LLLT) is suggested as a non-pharmacological and non-invasive treatment for dealing with painful conditions. The purpose of this study was to evaluate the pain relief effect of LLLT after endodontic treatment. METHODS: Eighty patients randomly received either LLLT (n=40), or placebo laser (n=40) after the completion of endodontic treatment for their first permanent upper or lower molars. In the laser group, the patients received a single course of low level laser therapy (Whitening Lase II- Laser DMC, Samsung, Korea) for 80 second (a dose = 70 j/cm²) per tooth. Intensity of post treatment pain was recorded using a questionnaire (The McGill Pain Questionnaire) and a numeric rating scale (Visual Analogue Scale VAS) at 4, 8, 12, 24, and 48 hours. VAS is a 10 cm line with “no pain” at one end, and “worst pain imaginable” at the other end. This method makes it possible to quantify pain levels. T-test and Chi-square test were used for data statistical analyses. RESULTS: Compared to the placebo group, post-endodontic pain was significantly reduced in LLLT group at 4, 8, 12, and 48 hours (P<0.05). But the difference between the two groups was not significant at 24 hours after endodontic treatment (P>0.05). CONCLUSION: Regarding the significant pain reduction in LLLT group at 4, 8, 12, and 48 hours after endodontic treatment, LLLT seems to be an effective and nonpharmacological approach for the reduction of post-endodontic treatment pain.